A Survey on the security of Cloud Storage System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Distributed computing is an emerging processing tool in software engineering today. Distributed computing is a collection of assets and services provided by a company or the internet. Different figuring approaches, such as matrix processing and dispersed registering, are broadened by distributed computing. Distributed computing is now used in both the modern and academic fields. Cloud encourages its customers by providing virtual assets through the internet. New procedures are emerging as the area of distributed computing expands. As the distributed computing environment grows, so do the security problems for cloud engineers. Since cloud clients save their data in the cloud, a lack of security in the cloud can jeopardise the client's trust. In this paper, we'll look at a few different aspects of cloud protection, such as multi-occupancy, versatility, and usability. We'll also look at current security strategies and techniques for a secure cloud. This paper will allow specialists and experts to consider the different security threats as well as the models and instruments that have been suggested.